High-temperature fatigue crack growth behavior of 17-4 PH stainless steels - Hsu, Kuei-Chang; Lin, Chih-Kuang (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2004)
The fatigue crack growth (FCG) behavior was investigated for 17-4 PH stainless steels in three heat-treated conditions, i.e., unaged (condition A), peak-aged (condition H900), and overaged (condition H1150), at temperatures ranging from 300 °C to 500 °C. The high-temperature fatigue crack growth rates (FCGRs) of condition H1150 were increased with an increase in temperature. However, for conditions A and H900 tested at 500 °C, the FCGRs were lower than the lower temperature ones. At 300 °C and 400 °C, H1150 and H900 generally showed the lowest and highest FCGRs, respectively, with condition A demonstrating behavior between the two. At 500 °C, the FCGR curves for all material conditions merged together. The anomalous FCG behavior of 17-4 PH stainless steels at 500 °C was mainly caused by an in-situ precipitate-coarsening effect during test. [PUBLICATION ABSTRACT]